An Analysis of Speech Act Used by Coronavirus Advertisement in Indonesian Ministry of Health - Novi Rina Dewi, M.Pd (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2021)
Language as a means of communication. Human beings always use it in interaction. They are many functions of language. With language, they can talk about culture, economic, education, politics, social, or anything that happens in their life. Therefore, it plays important role in social life. In daily written or spoken form of language which we use in communication, it consists of performing speech acts. According to Austin (1993), all expressions of language must be viewed as acts. He distinguished in three types, there are locution, illocution, and perlocution. The problem of this study is Whar are the classification of illusionary act used by advertisement of coronavirus in the Indonesian Ministry of health? The purposes of this study are to describe the classification of illocutionary acts used by advertisement of coronavirus in the Indonesian Ministry of health. In this research, the researcher uses descriptive qualitative based on its purpose and the type of the data. the result of this research is found two data of illocution between five kinds of illocution that She took from Searly’s theory. Those data were found are directives (commanding action, ordering action, and advising action) and assertive (informing things action), while the commisives, declarative and expressive were not found in those advertisements about coronavirus. Keywords : Language, Speech Act, and advertisement